‘Udaan’: TATA Salt’s endeavour to grow market share - TULI, Kapil R. (Institutional Knowledge at Singapore Management University, 2012)
This case is set in September 2007, and revolves around the Head of Sales & Marketing at Tata Chemicals Limited wondering how he could boost the market share of Tata Salt, one of the flagship products of the company. The dilemma is particularly interesting as Tata Salt had been ranked as the ‘Most Trusted Food Brand in India’ for the fourth year in a row and had very high brand equity – and yet its market share of 46% in the national branded segment and 18% in the total packaged iodised salt market, did not appear to grow in reflection of that high brand equity. Some of the key factors that the protagonist had to consider while devising a strategy was the complexity of the different markets within India across geographical areas, as well as the intensifying competition from other brands and types of salt. Through this case, students would have an opportunity to analyse the various alternatives available to the company for boosting market share, such as promotional pricing or launching an advertising push to strengthen the consumer pull for the brand. They would also understand the pros and cons of specific Key Performance Indicators, for instance boosting market share; and the challenges in implementing the 4 Ps, namely product, price, place and promotion.